White Female Victims and Death Penalty Disparity Research - Holcomb, Jeff (Justice quarterly, 2004)
Empirical studies of the death penalty continue to find that the race and gender of homicide victims are associated with the severity of legal responses in homicide cases even after controlling for legally relevant factors. A limitation of this research, however, is that victim race and gender are examined as distinct and independent factors in statistical models. In this study, we explore whether the independent examination of victim race and gender masks important differences in legal responses to homicides. In particular, we empirically test the hypothesis that defendants convicted of killing white females are significantly more likely to receive death sentences than killers of victims with other race-gender characteristics. Findings indicate that homicides with white female victims were more likely to result in death sentences than other victim race-gender dyads. We posit that this response may be unique and result in differential sentencing outcomes